2017
DOI: 10.15288/jsad.2017.78.608
|View full text |Cite
|
Sign up to set email alerts
|

Sharing of Alcohol-Related Content on Social Networking Sites: Frequency, Content, and Correlates

Abstract: First and foremost I want to thank my supervisors, Torbjørn and Ståle, for sharing their knowledge and for always being helpful and friendly. I want to thank Ståle for being reassuring, available, and inspiring, he has always made me feel much better every time I have felt unconfident or sad. I am also very happy that Torbjørn have been my supervisor, he has given me a great deal of support and time to discuss every possible issue from failing to get my driver license to statistical analyses. I am truly lucky … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
31
1
3

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(35 citation statements)
references
References 133 publications
0
31
1
3
Order By: Relevance
“…The association between disclosure and exposure and later alcohol use was mitigated when controlling for demographics and personality factors, and for other aspects of social media use. Disclosure and exposure have been or may be linked to certain demographic, personality, and social media use factors (e.g., being single, extroversion, strong social media engagement) which again have been linked to increased alcohol use (Merenakk et al, 2003 ; Andersson et al, 2007 ; Egan and Moreno, 2011 ; Beullens and Schepers, 2013 ; Nedregård and Olsen, 2014 ; Westgate et al, 2014 ; Erevik et al, 2017 ). The current results nevertheless suggest that the relationship between disclosure and exposure and later alcohol use cannot be fully attributed to such confounding factors.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The association between disclosure and exposure and later alcohol use was mitigated when controlling for demographics and personality factors, and for other aspects of social media use. Disclosure and exposure have been or may be linked to certain demographic, personality, and social media use factors (e.g., being single, extroversion, strong social media engagement) which again have been linked to increased alcohol use (Merenakk et al, 2003 ; Andersson et al, 2007 ; Egan and Moreno, 2011 ; Beullens and Schepers, 2013 ; Nedregård and Olsen, 2014 ; Westgate et al, 2014 ; Erevik et al, 2017 ). The current results nevertheless suggest that the relationship between disclosure and exposure and later alcohol use cannot be fully attributed to such confounding factors.…”
Section: Discussionmentioning
confidence: 99%
“…Certain characteristics seem to increase the likelihood of both disclosure and exposure of alcohol-related content on social media and high alcohol consumption (Westgate and Holliday, 2016 ). Status as single and extroversion are both positively associated with disclosure of alcohol-related content (Erevik et al, 2017 ) and alcohol consumption (Merenakk et al, 2003 ; Andersson et al, 2007 ; Raynor and Levine, 2009 ). Certain aspects of social media use, like the number of online-friends, seem also to be positively associated with disclosure and exposure and alcohol use (Egan and Moreno, 2011 ; Ridout et al, 2012 ; Beullens and Schepers, 2013 ; Moreno et al, 2014 ; Westgate et al, 2014 ; Westgate and Holliday, 2016 ).…”
Section: Introductionmentioning
confidence: 99%
“…Despite the public nature of social networking websites, they are a common outlet for individuals to discuss substance use (Boyle et al., ; Egan and Moreno, ; Griffiths and Casswell, ; Moreno et al., ). For example, a study of 11,236 university students found that 97% used social networking websites and that 71% of these students reported posting alcohol‐related content (Erevik et al., ). On Twitter specifically, Alhabash and colleagues () found that 2% of the nearly 50 million Tweets published in the United States in March 2015 included alcohol‐related content (Alhabash et al., ).…”
Section: Alcohol‐related Blackoutsmentioning
confidence: 99%
“…15 Observing others' post regarding solitary drinking on SNS can increase one's posting on SNS. In addition, considering that people strategically manage their impressions they make on SNS, 22,23 posting on SNS will be influenced by their norm perceptions and expectancies.…”
Section: Introductionmentioning
confidence: 99%